Vanellus chilensis subsp. chilensis chilensis (Molina 1782 - Gonza ́ Lez-Acun, Daniel A.; Palma, Ricardo L. (Zenodo, 2021)
Vanellus chilensis chilensis (Molina, 1782) Southern lapwing—Queltehue Actornithophilus gracilis (Piaget, 1880) Austromenopon aegialitidis (Durrant, 1906) sensu lato Quadraceps guimaraesi Timmerman, 1954 : Published as part of Gonza ́ Lez-Acun, Daniel A. & Palma, Ricardo L., 2021, An annotated catalogue of bird lice (Insecta: Phthiraptera) from Chile, pp. 1-151 in Zootaxa 5077 (1) on page 124, DOI: 10.11646/zootaxa.5077.1.1, http://zenodo.org/record/5766642 : {"references": ["Piaget, E. (1880) Les Pediculines. Essai Monographique. Two volumes. E. J. Brill, Leiden, xxxix + 714 pp., 56 pls.", "Durrant, E. P. (1906) Descriptions of new Mallophaga. The Ohio Naturalist, 6 (7), 528 - 530. https: // doi. org / 10.1111 / j. 1949 - 8594.1906. tb 02873. x"]}